2018
DOI: 10.1051/e3sconf/20184004010
|View full text |Cite
|
Sign up to set email alerts
|

Measuring bedload grain-size distributions with passive acoustic measurements

Abstract: Bedload Self-Generated Noise (SGN) measurements consist in deploying an underwater microphone (i.e. a hydrophone) in the water course and to record the ambient noise of a river. The use of hydrophones is of interest as it can be easily deployed and can provide a continuous monitoring of bedload transport. However, developments are still required to fully understand how bedload characteristics (e.g. specific flux or granulometry) are related to bedload SGN parameters (e.g. acoustic power and spectrum). Laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…(2018). However, the inversion results overestimate sampled values for five gravel‐bed (Geay, Zanker, Hauet, et al., 2018; Geay, Zanker, Petrut, et al., 2018), suggesting that the acoustic power measured in rivers may not adequately capture the finest materials contained in bedload.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…(2018). However, the inversion results overestimate sampled values for five gravel‐bed (Geay, Zanker, Hauet, et al., 2018; Geay, Zanker, Petrut, et al., 2018), suggesting that the acoustic power measured in rivers may not adequately capture the finest materials contained in bedload.…”
Section: Introductionmentioning
confidence: 77%
“…The first monitoring of bedload SGN by hydrophone was performed on the Isére River by Braudeau (1951) using a microphone connected to an amplifier. Following studies have demonstrated that the acoustic power of bedload SGN was mainly correlated to bedload flux in controlled experiments (Johnson & Muir, 1969; Thorne, 1986), and field studies (Barton et al., 2010; Geay, Zanker, Petrut, et al., 2018; Marineau et al., 2012). Moreover, the Power Spectral Density (PSD, the variation of power with frequency in Pa2Hz10.25em ${\text{Pa}}^{2}\cdot {\text{Hz}}^{\mbox{-}1}\hspace*{.5em}$) of the acoustic signal may also contain information on the transported diameters (Petrut et al., 2018; Thorne, 1986; Thorne & Foden, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations